2015
DOI: 10.1093/mnras/stu2721
|View full text |Cite
|
Sign up to set email alerts
|

Multiwaveband photometry of the irradiated brown dwarf WD0137−349B

Abstract: WD0137-349 is a white dwarf-brown dwarf binary system in a 116 minute orbit. We present radial velocity observations and multiwaveband photometry from V , R and I in the optical, to J, H and K s in the near-IR and [3.6], [4.5], [5.8] and [8.0] µm in the mid-IR. The photometry and lightcurves show variability in all wavebands, with the amplitude peaking at [4.5] microns, where the system is also brightest. Fluxes and brightness temperatures were computed for the heated and unheated atmosphere of the brown dwarf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
100
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(109 citation statements)
references
References 50 publications
7
100
0
Order By: Relevance
“…One obvious suggestion is that there is an additional absorbing molecule that is not included that absorbs in the mid-infrared, particularly in the [4.5] bandpass. The bright [3.6] point could be enhanced by an emission mechanism (e.g., Casewell et al 2015) that operates in that bandpass (but not at [4.5]). Both of these "additional molecule" explanations are speculative and require further study.…”
Section: Speculations On Missing Physicsmentioning
confidence: 99%
“…One obvious suggestion is that there is an additional absorbing molecule that is not included that absorbs in the mid-infrared, particularly in the [4.5] bandpass. The bright [3.6] point could be enhanced by an emission mechanism (e.g., Casewell et al 2015) that operates in that bandpass (but not at [4.5]). Both of these "additional molecule" explanations are speculative and require further study.…”
Section: Speculations On Missing Physicsmentioning
confidence: 99%
“…However, at 2 lm (K band) and at 4:5 lm, the flux of the brown dwarf is still much brighter than the model predicts. Casewell et al (2015) suggest that UV irradiation can cause photochemical reactions in the upper brown dwarf's atmosphere that produce large hydrocarbon molecules causing the brown dwarf to be brighter at 2 and 4:5 lm as were demonstrated for cosmic ray impact by Rimmer et al (2014).…”
Section: Multi-wavelength Observations Of Activity On Ultracool Dwarfsmentioning
confidence: 76%
“…Converting the dayside and nightside flux to brightness temperature (peak blackbody temperature with that flux at that wavelength) shows a temperature difference between the two hemispheres of $ 500 K, and a possible temperature inversion in the atmosphere. Casewell et al (2015) compare the observed photometry fluxes (i.e. radiative fluxes measured in a certain wavelength interval) to models of irradiated brown dwarfs and show that the data are best fit by models that incorporate fullenergy circulation around the brown dwarf, but do not contain a temperature inversion.…”
Section: Multi-wavelength Observations Of Activity On Ultracool Dwarfsmentioning
confidence: 99%
See 1 more Smart Citation
“…The compact orbits lead to tidally synchronous orbits and significant differences between dayside and nightside brown-dwarf surface temperatures (Casewell et al 2015). Despite the strong irradiation, the dayside temperatures (∼ 3000 K) are still too cool to explain the excesses seen in this region (Casewell et al 2015).…”
Section: Region Iii: High Tempertaure Small Radiusmentioning
confidence: 99%